GAMBARAN ANGKA KEMATIAN IBU DI RSUP. Prof. Dr. R. D. KANDOU MANADO PERIODE JANUARI 2014 – SEPTEMBER 2015 - Andini, Ria Mariani; Sondakh, Joice; Laihad, Bismarch J. (Universitas Sam Ratulangi, 2016)
Abstract: Maternal mortality is a complex problem that is caused by a variety of causes that can be distinguished on the determinant of near, intermediate and far. Maternal mortality or maternal death is one indicator to see the progress of the health of a country, especially with regard to maternal and child health issues. The research objective was to determine the description of Maternal Mortality Rate (MMR) in RSUP Prof. Dr. dr. R. D. Kandou Manado period January 2014 - September 2015. Methods: This study is a retrospective descriptive study. The population is all deliveries in RSUP Prof. Dr. dr. R. D. Kandou Manado period January 2014 - September 2015. The samples is 20 persons, sampling with total sampling technique. Results: based on this research, the highest number of births was in 2014 that as many as 3,347 people (70.8%), while in 2015 as many as 1,380 people (29.2%). Maternal Mortality Ratio (MMR) was 298 per 100,000 live births in 2014 and 725 per 100,000 live births in 2015. The number of maternal deaths in the period from January 2014 through September 2015 respectively by 10 people (50%). The most diagnosis entry patients is eclampsia by 10 persons (50.0%) Based on the causes of maternal mortality, that most because of hemorrhagic stroke by 7 people (35.0%).. Conclusion: Maternal Mortality Ratio (MMR) was 298 per 100,000 live births in 2014 and 725 per 100,000 live births in 2015. By entering the patient's diagnosis, most of the patients with the diagnosis of eclampsia and cause most maternal deaths are patients who died because stroke hemorrhagic period January 2014 through September 2015.Keyword: Maternal Mortality RateAbstrak: Kematian ibu merupakan salah satu indikator untuk melihat kemajuan kesehatan suatu negara, khususnya yang berkaitan dengan masalah kesehatan ibu dan anak. Tujuan penelitian adalah mengetahui gambaran Angka Kematian Ibu (AKI) di RSUP. Prof. Dr. R. D. Kandou Manado Periode Januari 2014 – September 2015. Metode: penelitian ini merupakan jenis penelitian deskriptif retrospektif. Populasi yang diambil adalah semua persalinan di RSUP. Prof. Dr. R. D. Kandou Manado Periode Januari 2014 – September 2015. Jumlah sampel adalah 20 orang, penentuan sampel dengan teknik total sampling. Hasil: berdasarkan hasil penelitian, jumlah persalinan terbanyak adalah pada tahun 2014 yaitu sebanyak 3.347 orang (70,8%) sedangkan pada tahun 2015 sebanyak 1.380 orang (29,2%). Rasio Angka Kematian Ibu (AKI) 298 per 100.000 kelahiran hidup pada tahun 2014 dan 725 per 100.000 kelahiran hidup pada tahun 2015.Sedangkan jumlah Jumlah Kematian Ibu pada periode januari 2014 sampai september 2015 masing-masing sebanyak 10 orang (50%). Diagnosa masuk pasien terbanyak yaitu eklamsia sebesar 10 orang (50,0%) Berdasarkan penyebab kematian ibu, yang tebanyak karena stroke hemoragik sebesar 7 orang (35,0%). Kesimpulan: Rasio Angka Kematian Ibu (AKI) adalah 298 per 100.000 kelahiran hidup pada tahun 2014 dan 725 per 100.000 kelahiran hidup pada tahun 2015. Berdasarkan diagnosis masuk pasien, terbanyak adalah pasien dengan diagnosa eklampsia dan penyebab kematian ibu terbanyak adalah pasien yang meninggal karena stroke hemoragik periode januari 2014 sampai september 2015.Kata kunci: Angka Kematian Ibu